WATER QUALITY OF THE BULAVIN RIVER (UKRAINE) AND CONDITIONS OF MAN-MADE TRANSFORMATION - Lialiuk, Natalia (European Science, 2023)
The hydrochemical parameters and pollutants of the Bulavin River (Ukraine) were studied. The water quality in the middle stream has been established. In the studied areas (near the city of Yenakieve), the river water for the period from 2002 to 2008 was a